High temperature resistant uv debonding adhesive and preparation method thereof
Patent Information
- Application Number
- CN202311751294.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-19
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-12-19
AI Technical Summary
[0004]上述专利文献中的UV减粘胶的耐高温性能不佳,高温会导致减粘胶的粘结性急剧下降,使得被加工物体在加工时脱落,影响被加工物体的正常加工
[0022]1. The high-temperature resistant UV-resistant adhesive processed using the raw material formula of this invention can effectively enhance the high-temperature resistance of the UV-resistant adhesive, ensuring that it maintains good tack at 150°C. This effectively prevents a sharp decline in adhesion in high-temperature working environments, avoiding the detachment of processed objects during processing and ensuring normal processing. By adjusting and modifying the adhesive's components, processes, and monomers, high-temperature resistance is improved, preventing defects such as decreased adhesion and shrinkage due to high temperatures. After processing, the adhesive strength can be instantly reduced by ultraviolet radiation. A heat-resistant acrylic resin was synthesized via free radical solution polymerization using maleic anhydride, methyl methacrylate, and methacrylic acid as monomers, azobisisobutyronitrile as an initiator, and isopropanol as a solvent. The content of maleic anhydride... The most significant impact is on temperature resistance. With increasing maleic anhydride content, the heat resistance of the heat-resistant acrylic resin is significantly improved, and increasing the amount of maleic anhydride in the formulation helps improve monomer conversion rate and solid content. However, if the proportion of maleic anhydride is too high, it will lead to a low proportion of other monomers, which is not conducive to the polymerization reaction and the formation of heat-resistant acrylic resin. Siloxane monomers, with Si-O-Si as the backbone, can effectively add Si-O-Si chains to the tack reducer, thereby effectively improving the high-temperature resistance of the UV tack reducer. Siloxane monomer molecular chains have a flexible and extensible helical structure, with small intermolecular forces, good flexibility, and low surface energy. They possess waterproof, defoaming, and release properties, which can improve the high-temperature resistance of the UV tack reducer without affecting its normal UV curing and peeling performance.
Smart Images

Figure BDA0004615875030000071
Abstract
Description
Technical Field
[0001] This invention relates to the field of UV anti-tack adhesive technology, and more specifically, to a high-temperature resistant UV anti-tack adhesive and its preparation method. Background Technology
[0002] UV-resistant adhesive is a new type of adhesive material with extremely high adhesion, ensuring that the bonded object remains stable during processing, without detachment or flaking, and also protecting the unprocessed parts. After processing, ultraviolet radiation instantly reduces its adhesion, allowing the object to be easily removed from the bonded material without affecting its performance.
[0003] Patent (CN114644900B) discloses a UV-reducing adhesive composition, a UV-reducing adhesive tape, and a method for preparing the UV-reducing adhesive tape. The UV-reducing adhesive composition comprises: 50-100 parts by weight of a carboxyl-containing acrylate pressure-sensitive adhesive, 2-50 parts by weight of a multifunctional acrylate compound, 1-20 parts by weight of an additive, 0.001-0.5 parts by weight of a curing agent, 0.001-0.5 parts by weight of a curing accelerator, and 0.1-3 parts by weight of a photoinitiator; wherein the additive contains an active group, and the active group includes at least one of epoxy and amino groups. Thus, the components functionally support and cooperate with each other, enabling the composition of this invention to graft double bonds onto the side chains of the pressure-sensitive adhesive during the curing process, thereby increasing the molecular weight and reducing residue. Furthermore, this method has advantages such as simple process, energy saving, and long storage time.
[0004] The UV-resistant adhesive in the aforementioned patent documents has poor high-temperature resistance. High temperatures will cause the adhesive properties of the adhesive to drop sharply, causing the processed object to fall off during processing and affecting the normal processing of the processed object. Summary of the Invention
[0005] To overcome the above-mentioned defects of the prior art, embodiments of the present invention provide a high-temperature resistant UV-resistant adhesive and its preparation method.
[0006] A high-temperature resistant UV-resistant adhesive comprises, by weight percentage: 34.2-34.8% UV photosensitive monomer, 2.0-2.2% photoinitiator, 1.2-1.3% curing agent, and the remainder being modified acrylic resin.
[0007] Furthermore, the UV photosensitive monomer is one or more of the following: hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, and ethoxylated trimethylolpropane triacrylate.
[0008] Furthermore, the photoinitiator is one or more of the following: 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-methylphenylpropane-1-one, benzoin dimethyl ether, benzophenone, 2-isopropylthioxanthone, and ethyl 2,4,6-(trimethylbenzoyl)phosphonate.
[0009] Furthermore, the curing agent is one or more of the following: triphenylmethane triisocyanate, toluene diisocyanate trimer, hexamethylene diisocyanate trimer, and isophorone diisocyanate trimer, in combination.
[0010] Furthermore, the modified acrylic resin comprises, by weight percentage: 20.5–21.1% maleic anhydride, 18.3–18.7% methyl methacrylate, 6.8–7.2% methacrylic acid, 0.34–0.40% azobisisobutyronitrile, 6.8–7.2% siloxane monomer, with the remainder being isopropanol.
[0011] Furthermore, the siloxane monomer is one or a blend of one or both of the following: a monoacrylate-based polysiloxane and a monomethacrylate-based polysiloxane.
[0012] Furthermore, the high-temperature resistant UV-resistant adhesive comprises, by weight percentage: 34.4–34.6% UV photosensitive monomer, 2.05–2.15% photoinitiator, 1.23–1.27% curing agent, with the remainder being modified acrylic resin; the modified acrylic resin comprises, by weight percentage: 20.7–20.9% maleic anhydride, 18.4–18.6% methyl methacrylate, 6.9–7.1% methacrylic acid, 0.36–0.38% azobisisobutyronitrile, 6.9–7.1% siloxane monomer, with the remainder being isopropanol.
[0013] Furthermore, the high-temperature resistant UV-resistant adhesive comprises, by weight percentage: 34.5% UV photosensitive monomer, 2.1% photoinitiator, 1.25% curing agent, and the remainder being modified acrylic resin; the modified acrylic resin comprises, by weight percentage: 20.8% maleic anhydride, 18.5% methyl methacrylate, 7.0% methacrylic acid, 0.37% azobisisobutyronitrile, 7.0% siloxane monomer, and the remainder being isopropanol.
[0014] This invention also provides a method for preparing a high-temperature resistant UV-resistant adhesive, the specific preparation steps of which are as follows:
[0015] Step 1: Weigh out the following components from the UV photosensitive monomer, photoinitiator, curing agent, and modified acrylic resin raw material: maleic anhydride, methyl methacrylate, methacrylic acid, azobisisobutyronitrile, siloxane monomer, and isopropanol.
[0016] Step 2: Mix maleic anhydride, methyl methacrylate, methacrylic acid and azobisisobutyronitrile from Step 1 until homogeneous to obtain material A;
[0017] Step 3: Heat and keep the isopropanol from Step 1 at a constant temperature, then slowly add half the weight of material A from Step 2 to the isopropanol. After the addition is complete, material B is obtained.
[0018] Step 4: Heat and keep the material B obtained in Step 3, then add the siloxane monomer from Step 1, stir and sonicate for 10-20 minutes, continue to add the remaining material A from Step 2, react at a constant temperature for 2-3 hours, and then cool down to obtain the modified acrylic resin.
[0019] Step 5: The UV photosensitive monomer, photoinitiator, curing agent from Step 1 and the modified acrylic resin from Step 4 are blended and stirred to obtain a high-temperature resistant UV-resistant adhesive.
[0020] Furthermore, in step two, the stirring speed is 600–800 r / min; in step three, the heating and holding temperature of isopropanol is 40–50 °C, and the dropping time is 30–40 min; in step four, the heating and holding temperature is 80–85 °C, the stirring speed is 200–400 r / min, the ultrasonic power is 600–800 W, the ultrasonic treatment frequency is 1.5–1.7 MHz, and the isothermal reaction temperature is 80–85 °C; in step five, stirring is carried out under yellow light, the stirring speed is 300–500 r / min, and the stirring time is 30–40 min.
[0021] The technical effects and advantages of this invention are as follows:
[0022] 1. The high-temperature resistant UV-resistant adhesive processed using the raw material formula of this invention can effectively enhance the high-temperature resistance of the UV-resistant adhesive, ensuring that it maintains good tack at 150°C. This effectively prevents a sharp decline in adhesion in high-temperature working environments, avoiding the detachment of processed objects during processing and ensuring normal processing. By adjusting and modifying the adhesive's components, processes, and monomers, high-temperature resistance is improved, preventing defects such as decreased adhesion and shrinkage due to high temperatures. After processing, the adhesive strength can be instantly reduced by ultraviolet radiation. A heat-resistant acrylic resin was synthesized via free radical solution polymerization using maleic anhydride, methyl methacrylate, and methacrylic acid as monomers, azobisisobutyronitrile as an initiator, and isopropanol as a solvent. The content of maleic anhydride... The most significant impact is on temperature resistance. With increasing maleic anhydride content, the heat resistance of the heat-resistant acrylic resin is significantly improved, and increasing the amount of maleic anhydride in the formulation helps improve monomer conversion rate and solid content. However, if the proportion of maleic anhydride is too high, it will lead to a low proportion of other monomers, which is not conducive to the polymerization reaction and the formation of heat-resistant acrylic resin. Siloxane monomers, with Si-O-Si as the backbone, can effectively add Si-O-Si chains to the tack reducer, thereby effectively improving the high-temperature resistance of the UV tack reducer. Siloxane monomer molecular chains have a flexible and extensible helical structure, with small intermolecular forces, good flexibility, and low surface energy. They possess waterproof, defoaming, and release properties, which can improve the high-temperature resistance of the UV tack reducer without affecting its normal UV curing and peeling performance.
[0023] 2. In the process of processing high-temperature resistant UV-resistant adhesives, maleic anhydride, methyl methacrylate, methacrylic acid, and azobisisobutyronitrile are stirred and mixed evenly to prepare the raw materials for the reaction, facilitating the subsequent polymerization reaction of the three monomers. Isopropanol is first heated to provide suitable reaction conditions for material A, making the polymerization reaction more stable. Material A is then added dropwise to isopropanol for a rapid and stable polymerization reaction. After half of material A has undergone polymerization, siloxane monomers are added, followed by stirring and ultrasonic treatment, which effectively improves the uniform distribution of siloxane monomers in material B. Then, the remaining material A is added dropwise, so that siloxane monomers are added during the original polymerization reaction. This allows for further grafting of siloxane monomers into the heat-resistant acrylic resin, which can effectively enhance the high-temperature resistance of the resin. As the reaction time increases, the conversion rate increases, leading to more chains transferring to larger molecular weights, and the temperature resistance also increases accordingly. However, once the molecular weight increases to a certain extent, it no longer increases with reaction time, and the temperature resistance of the synthesized resin no longer improves. By blending and stirring the UV photosensitive monomer, photoinitiator, curing agent, and modified acrylic resin, a high-temperature resistant UV-resistant adhesive is obtained. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1:
[0026] This invention provides a high-temperature resistant UV-resistant adhesive, comprising, by weight percentage: 34.2% UV photosensitive monomer, 2.0% photoinitiator, 1.2% curing agent, and the remainder being modified acrylic resin; wherein the modified acrylic resin comprises, by weight percentage: 20.5% maleic anhydride, 18.3% methyl methacrylate, 6.8% methacrylic acid, 0.34% azobisisobutyronitrile, 6.8% siloxane monomer, and the remainder being isopropanol;
[0027] The UV photosensitive monomer is hydroxyethyl acrylate; the photoinitiator is 1-hydroxycyclohexylphenyl ketone; the curing agent is triphenylmethane triisocyanate; and the siloxane monomer is a single-terminated acrylate-based polysiloxane.
[0028] This invention also provides a method for preparing a high-temperature resistant UV-resistant adhesive, the specific preparation steps of which are as follows:
[0029] Step 1: Weigh out the following components from the UV photosensitive monomer, photoinitiator, curing agent, and modified acrylic resin raw material: maleic anhydride, methyl methacrylate, methacrylic acid, azobisisobutyronitrile, siloxane monomer, and isopropanol.
[0030] Step 2: Mix maleic anhydride, methyl methacrylate, methacrylic acid and azobisisobutyronitrile from Step 1 until homogeneous to obtain material A;
[0031] Step 3: Heat and keep the isopropanol from Step 1 at a constant temperature, then slowly add half the weight of material A from Step 2 to the isopropanol. After the addition is complete, material B is obtained.
[0032] Step 4: Heat and keep the material B obtained in Step 3 at a constant temperature, then add the siloxane monomer from Step 1, stir and sonicate for 15 minutes, continue to add the remaining material A from Step 2, react at a constant temperature for 2.5 hours, and then cool down to obtain the modified acrylic resin.
[0033] Step 5: The UV photosensitive monomer, photoinitiator, curing agent from Step 1 and the modified acrylic resin from Step 4 are blended and stirred to obtain a high-temperature resistant UV-resistant adhesive.
[0034] In step two, the stirring speed is 600 r / min; in step three, the isopropanol is heated and kept at a temperature of 40°C for 30 min; in step four, the heating and keeping temperature is 80°C, the stirring speed is 200 r / min, the ultrasonic power is 600 W, the ultrasonic treatment frequency is 1.5 MHz, and the constant temperature reaction temperature is 80°C; in step five, the mixture is stirred under yellow light at a stirring speed of 300 r / min for 30 min.
[0035] Example 2:
[0036] Unlike Example 1, the high-temperature resistant UV-resistant adhesive comprises, by weight percentage: 34.8% UV photosensitive monomer, 2.2% photoinitiator, 1.3% curing agent, and the remainder being modified acrylic resin; the modified acrylic resin comprises, by weight percentage: 21.1% maleic anhydride, 18.7% methyl methacrylate, 7.2% methacrylic acid, 0.40% azobisisobutyronitrile, 7.2% siloxane monomer, and the remainder being isopropanol.
[0037] Example 3:
[0038] Unlike Examples 1-2, the high-temperature resistant UV-resistant adhesive comprises, by weight percentage: 34.5% UV photosensitive monomer, 2.1% photoinitiator, 1.25% curing agent, and the remainder being modified acrylic resin; the modified acrylic resin comprises, by weight percentage: 20.8% maleic anhydride, 18.5% methyl methacrylate, 7.0% methacrylic acid, 0.37% azobisisobutyronitrile, 7.0% siloxane monomer, and the remainder being isopropanol.
[0039] Example 4:
[0040] Unlike Example 3, in step two, the stirring speed was 700 r / min; in step three, the heating and holding temperature of isopropanol was 45°C, and the dropping time was 35 min; in step four, the heating and holding temperature was 83°C, the stirring speed was 300 r / min, the ultrasonic power was 700 W, the ultrasonic treatment frequency was 1.6 MHz, and the isothermal reaction temperature was 83°C; in step five, stirring was carried out under yellow light, the stirring speed was 400 r / min, and the stirring time was 35 min.
[0041] Comparative Example 1:
[0042] Unlike Example 4, the high-temperature resistant UV-resistant adhesive comprises, by weight percentage: 34.5% UV photosensitive monomer, 2.1% photoinitiator, 1.25% curing agent, and the remainder is modified acrylic resin; the modified acrylic resin comprises, by weight percentage: 18.5% methyl methacrylate, 7.0% methacrylic acid, 0.37% azobisisobutyronitrile, 7.0% siloxane monomer, and the remainder isopropanol.
[0043] Comparative Example 2:
[0044] Unlike Example 4, the high-temperature resistant UV-resistant adhesive comprises, by weight percentage: 34.5% UV photosensitive monomer, 2.1% photoinitiator, 1.25% curing agent, and the remainder is modified acrylic resin; the modified acrylic resin comprises, by weight percentage: 20.8% maleic anhydride, 18.5% methyl methacrylate, 7.0% methacrylic acid, 0.37% azobisisobutyronitrile, and the remainder isopropanol.
[0045] Comparative Example 3:
[0046] Unlike Example 4, the preparation method of the high-temperature resistant UV-resistant adhesive includes the following specific steps:
[0047] Step 1: Weigh out the following components from the UV photosensitive monomer, photoinitiator, curing agent, and modified acrylic resin raw material: maleic anhydride, methyl methacrylate, methacrylic acid, azobisisobutyronitrile, siloxane monomer, and isopropanol.
[0048] Step 2: Stir and sonicate the maleic anhydride, methyl methacrylate, methacrylic acid, azobisisobutyronitrile, isopropanol and siloxane monomer from Step 1 for 15 min, keep at a constant temperature for 2.5 hours, and then cool down to obtain the modified acrylic resin.
[0049] Step 3: The UV photosensitive monomer, photoinitiator, curing agent from Step 1 and the modified acrylic resin from Step 2 are blended and stirred to obtain a high-temperature resistant UV adhesive.
[0050] In step two, the stirring speed is 300 r / min, the ultrasonic power is 700 W, the ultrasonic treatment frequency is 1.6 MHz, and the constant temperature reaction temperature is 83 ℃; in step three, stirring is carried out under yellow light, the stirring speed is 400 r / min, and the stirring time is 35 min.
[0051] Comparative Example 4:
[0052] Unlike Example 4, the preparation method of the high-temperature resistant UV-resistant adhesive includes the following specific steps:
[0053] Step 1: Weigh out the following components from the UV photosensitive monomer, photoinitiator, curing agent, and modified acrylic resin raw material: maleic anhydride, methyl methacrylate, methacrylic acid, azobisisobutyronitrile, siloxane monomer, and isopropanol.
[0054] Step 2: Mix maleic anhydride, methyl methacrylate, methacrylic acid, azobisisobutyronitrile and siloxane monomer from Step 1 until homogeneous to obtain material A;
[0055] Step 3: Heat and keep the isopropanol from Step 1 at a constant temperature, then slowly add half the weight of material A from Step 2 to the isopropanol. After the addition is complete, material B is obtained.
[0056] Step 4: Heat and keep warm the material B obtained in Step 3, stir and sonicate for 10-20 minutes, continue to add the remaining material A from Step 2, react at a constant temperature for 2-3 hours, and then cool down to obtain the modified acrylic resin.
[0057] Step 5: The UV photosensitive monomer, photoinitiator, curing agent from Step 1 and the modified acrylic resin from Step 4 are blended and stirred to obtain a high-temperature resistant UV adhesive.
[0058] In step two, the stirring speed is 700 r / min; in step three, the isopropanol is heated and kept at a temperature of 45°C for 35 min; in step four, the heating and keeping temperature is 83°C, the stirring speed is 300 r / min, the ultrasonic power is 700 W, the ultrasonic treatment frequency is 1.6 MHz, and the isothermal reaction temperature is 83°C; in step five, the mixture is stirred under yellow light at a stirring speed of 400 r / min for 35 min.
[0059] In the comparative examples and embodiments above: maleic anhydride was purchased from Shanghai Mairui Biochemical Technology Co., Ltd., item number: M01695; methyl methacrylate was purchased from Shandong Yanshuo Chemical Co., Ltd., item number: YS025; methacrylic acid was purchased from Shandong Yukang Chemical Co., Ltd., item number: 164; azobisisobutyronitrile was purchased from Shandong Yukang Chemical Co., Ltd., item number: 54; single-terminated acrylate polysiloxane was purchased from Guangzhou Ruiju Co., Ltd., single-terminated acrylate organosilicon DCA-2205, with a number average molecular weight of 800; hydroxyethyl acrylate was purchased from Shandong Yukang Chemical Co., Ltd., item number: 15; 1-hydroxycyclohexylphenyl ketone was purchased from Hubei Zhenbo Chemical Co., Ltd., item number: ZB68603; triphenylmethane triisocyanate was purchased from Tianmen Hengchang Chemical Co., Ltd., item number: HC2201; isopropanol was purchased from Shandong Yanshuo Chemical Co., Ltd., item number: YS046.
[0060] The high-temperature resistant UV anti-adhesive adhesive used in the comparative examples and embodiments of this invention is coated on the corona-electrode surface of the substrate layer and dried at 100°C for 2 minutes to form a UV anti-adhesive layer on the surface of the substrate layer with a thickness of 20 μm. The release surface of the release film layer is then bonded to the surface of the UV anti-adhesive layer away from the substrate layer and cured at 50°C for 3 days to obtain the UV anti-adhesive tape.
[0061] The UV-resistant adhesive tape was tested as follows: Adhesion holding power: According to GB / T 4851-1998, using an adhesive strength tester at 40℃ and a 500g weight; Heat-resistant adhesion holding power: According to GB / T 4851-1998, using an adhesive strength tester at 150℃ and a 500g weight; 180° peel strength was tested according to national standard GB / T2792; 180° peel strength after UV irradiation was tested using an LED UV lamp (wavelength 365nm) according to national standard GB / T2792, and the results are shown in Table 1.
[0062] Table 1:
[0063]
[0064] As shown in the table above, the high-temperature resistant UV adhesive of the present invention can effectively enhance the high-temperature resistance of UV adhesives, ensuring that the UV adhesives can maintain good tack at 150°C. It can effectively prevent the UV adhesives from rapidly decreasing in adhesion in high-temperature working environments, prevent the processed objects from falling off during processing, and ensure the normal processing of the processed objects. By adjusting and modifying the components, processes, and monomers of the adhesive, the high-temperature resistance is improved, avoiding defects such as decreased adhesion and shrinkage caused by high temperatures. After processing, the adhesion can be instantly reduced by ultraviolet radiation.
[0065] In this invention, a heat-resistant acrylic resin was synthesized via free radical solution polymerization using maleic anhydride, methyl methacrylate, and methacrylic acid as monomers, azobisisobutyronitrile as an initiator, and isopropanol as a solvent. The content of maleic anhydride has the most significant impact on the heat resistance. As the content of maleic anhydride increases, the heat resistance of the heat-resistant acrylic resin is significantly improved, and increasing the amount of maleic anhydride in the formulation helps to improve the monomer conversion rate and solid content. However, if the proportion of maleic anhydride is too high, it will lead to a low proportion of other monomers, which is detrimental to the polymerization reaction. A heat-resistant acrylic resin should be generated; the siloxane monomer, with Si-O-Si as its backbone, can effectively incorporate Si-O-Si chains into the anti-tack adhesive, thereby effectively improving the high-temperature resistance of the UV anti-tack adhesive; the siloxane monomer molecular chain segments have a flexible and stretchable helical structure, with small intermolecular forces, good flexibility, and low surface energy, possessing waterproof, defoaming, and release properties, which can improve the high-temperature resistance of the UV anti-tack adhesive without affecting its normal UV curing and peeling performance; in step two, maleic anhydride, methyl methacrylate, methacrylic acid, and azo dyes are added... Diisobutyronitrile (DIBN) is stirred and mixed evenly to prepare the raw material for the subsequent polymerization of the three monomers. In step three, isopropanol is first heated to provide suitable reaction conditions for material A, making the polymerization reaction more stable. Material A is then added dropwise to isopropanol for rapid and stable polymerization. In step four, after half of material A has undergone polymerization, siloxane monomers are added, and the mixture is stirred and ultrasonically treated to effectively improve the uniformity of siloxane monomer distribution in material B. Then, the remaining material A is added dropwise again to further improve the uniformity of the original distribution. Adding siloxane monomers during the polymerization reaction can further graft siloxane monomers onto the heat-resistant acrylic resin, effectively enhancing its high-temperature resistance. As the reaction time increases, the conversion rate improves, leading to more chain transfer to larger molecular weights, which in turn improves the temperature resistance. However, once the molecular weight reaches a certain level, it no longer increases with reaction time, and the temperature resistance of the synthesized resin no longer improves. In step five, the UV photosensitive monomer, photoinitiator, curing agent, and modified acrylic resin are blended and stirred to obtain a high-temperature resistant UV-resistant adhesive.
[0066] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-temperature resistant UV-resistant adhesive, characterized in that: The raw materials of the modified acrylic resin, calculated by weight percentage, include: 34.2-34.8% UV photosensitive monomer, 2.0-2.2% photoinitiator, 1.2-1.3% curing agent, and the remainder being modified acrylic resin; the UV photosensitive monomer is one or more of the following: hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, and ethoxylated trimethylolpropane triacrylate; the raw materials of the modified acrylic resin, calculated by weight percentage, include: 20.5-21.1% maleic anhydride, 18.3-18.7% methyl methacrylate, 6.8-7.2% methacrylic acid, 0.34-0.40% azobisisobutyronitrile, 6.8-7.2% siloxane monomer, and the remainder being isopropanol.
2. The high-temperature resistant UV-resistant adhesive according to claim 1, characterized in that: The photoinitiator is one or more of the following: 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-methylphenylpropane-1-one, benzoin dimethyl ether, benzophenone, 2-isopropylthioxanthone, and ethyl 2,4,6-(trimethylbenzoyl)phosphonate.
3. The high-temperature resistant UV-resistant adhesive according to claim 1, characterized in that: The curing agent is one or more of the following: triphenylmethane triisocyanate, toluene diisocyanate trimer, hexamethylene diisocyanate trimer, and isophorone diisocyanate trimer, in combination.
4. The high-temperature resistant UV-resistant adhesive according to claim 1, characterized in that: The siloxane monomer is one or a blend of one or both of the following: single-terminated acrylate-based polysiloxane and single-terminated methacrylate-based polysiloxane.
5. The high-temperature resistant UV-resistant adhesive according to claim 1, characterized in that: The raw materials of the modified acrylic resin, calculated by weight percentage, include: 34.4-34.6% UV photosensitive monomer, 2.05-2.15% photoinitiator, 1.23-1.27% curing agent, and the remainder being modified acrylic resin; the raw materials of the modified acrylic resin, calculated by weight percentage, include: 20.7-20.9% maleic anhydride, 18.4-18.6% methyl methacrylate, 6.9-7.1% methacrylic acid, 0.36-0.38% azobisisobutyronitrile, 6.9-7.1% siloxane monomer, and the remainder being isopropanol.
6. The high-temperature resistant UV-resistant adhesive according to claim 1, characterized in that: The raw materials of the modified acrylic resin, calculated by weight percentage, include: 34.5% UV photosensitive monomer, 2.1% photoinitiator, 1.25% curing agent, and the remainder being modified acrylic resin; the raw materials of the modified acrylic resin, calculated by weight percentage, include: 20.8% maleic anhydride, 18.5% methyl methacrylate, 7.0% methacrylic acid, 0.37% azobisisobutyronitrile, 7.0% siloxane monomer, and the remainder being isopropanol.
7. A method for preparing a high-temperature resistant UV-resistant adhesive according to any one of claims 1-6, characterized in that: The specific preparation steps are as follows: Step 1: Weigh out the following components from the UV photosensitive monomer, photoinitiator, curing agent, and modified acrylic resin raw material: maleic anhydride, methyl methacrylate, methacrylic acid, azobisisobutyronitrile, siloxane monomer, and isopropanol. Step 2: Mix maleic anhydride, methyl methacrylate, methacrylic acid and azobisisobutyronitrile from Step 1 until homogeneous to obtain material A; Step 3: Heat and keep the isopropanol from Step 1 at a constant temperature, then slowly add half the weight of material A from Step 2 to the isopropanol. After the addition is complete, material B is obtained. Step 4: Heat and keep the material B obtained in Step 3, then add the siloxane monomer from Step 1, stir and sonicate for 10-20 minutes, continue to add the remaining material A from Step 2, react at a constant temperature for 2-3 hours, and then cool down to obtain the modified acrylic resin. Step 5: The UV photosensitive monomer, photoinitiator, curing agent from Step 1 and the modified acrylic resin from Step 4 are blended and stirred to obtain a high-temperature resistant UV-resistant adhesive.
8. The method for preparing a high-temperature resistant UV-resistant adhesive according to claim 7, characterized in that: In step two, the stirring speed is 600–800 r / min; in step three, the heating and holding temperature of isopropanol is 40–50 °C, and the dropping time is 30–40 min; in step four, the heating and holding temperature is 80–85 °C, the stirring speed is 200–400 r / min, the ultrasonic power is 600–800 W, the ultrasonic treatment frequency is 1.5–1.7 MHz, and the isothermal reaction temperature is 80–85 °C; in step five, stirring is carried out under yellow light, the stirring speed is 300–500 r / min, and the stirring time is 30–40 min.
Citation Information
Patent Citations
UV anti-adhesion composition, UV anti-adhesion tape, and method for preparing UV anti-adhesion tape
CN114644900B
Preparation method of visible light resistant single-component UV (ultraviolet) viscosity reducing protection film
CN109735256A
Antistatic UV viscosity-reducing adhesive and preparation method thereof
CN114133879A